OMEGA 3 SUPPLEMENTATION DECREASE A BLOOD CHOLESTROL LEVEL IN TRAINED WOMEN - Diana Rahima; Bambang Purwanto; Sri Ratna Dwiningsih (Indonesian Midwifery and Health Sciences Journal, 2021)
AbstractBackground : Trained woean who experiencing menstrual disoders are found with high blood cholesterol level. This situation is contrary to who don’t experience menstrual disorder. Mentrual disorder condition has a low estrogen level. The low estrogen level is associated with endothelial disfunction which causes blood cholesterol increase. The benefit of omega 3 supplementation have been clinically proven to prevent atherosclerosis, decrease blood cholesterol levels, and playong an important role in modulating inflamation. Omega 3 supplementation is expected to decrease blood cholesterol levels in trained women. Method: This research is using field experimental with case control method. The samples are 30 trained womens contained by 15 are controlled and 15 are given treatment. The sampling technique is randomized allocation. The independent variabel is omega 3 300mg supplementation and the dependent variabel is blood cholesterol levels. Data are analized using parametric statistic paired T-test. Result: The bivariate analysis showed there is a meaningful difference on blood cholesterol levels in the treatment group p=0,0027 and no change in control group p=0,191 during treatment for 8 weeks. Conclusion: Omega 3 supplementation decrease a blood cholesterol levels in trained women.